Asuhan Keperawatan Pada Bayi dengan Diare Akut : Sebuah Studi Kasus - Fitri Nurbaiti sobari (AKPER Pasar Rebo, 2020)
Background : Diarrhea is a disease of the digestive tract caused by several factors namely infection, malabsorption, food and psychological which usually occurs in children in Indonesia. Methods : The method used is a qualitative method, the time of February 2020 and the place of research in Pasar Minggu Regional General Hospital. Result : The diagnosis that arises in the case of fluid volume deficiency is associated with active fluid loss, nutritional imbalance less than the body's needs is related to inadequate food intake and hyperthermia is associated with fungal infection factors. Conclusion : Implementation of nursing care in accordance with the nursing process will get results that are in accordance with predetermined outcome criteria to achieve success nursing care requires good cooperation between health workers with patients or families.